Regional Development of Tourism in Ponorogo Regency, East Java - Yusuf Adam Hilman (Program Pascasarjana, 2016)
Ponorogo Regency in East Java has natural resources, as well as the potential typical culture, and a society that can be developed into tourism attractions. This study was aimed to assess these potentials that can be then optimally developed, with factors that support the construction of tourism in Regency of Ponorogo. In carrying out the development of tourism in Ponorogo, there are several constraint or barrier factors, including access to transportation facilities and infrastructure which are still minimum and not optimal, access of the road and cross facilities is still less than the expectation, make it difficult for visitors to access tourism in Ponorogo. To solve this problem, we should implement the good cooperations, for all parties to jointly together in solving those problems.Â Keywords: community development, development of tourism, potential of the region.